Biomechanical comparison of four different fixation methods in the management of Pauwels type III femoral neck fractures: Is there a clear winner? - Yildirim, Cem; Demirel, Mehmet; Karahan, Gökhan; Cetinkaya, Engin; Misir, Abdülhamit; Yamak, Fatih; Bozdağ, Ergün (Elsevier BV, 2022)
Cannulated screws augmented with the medial buttress plate could confer greater biomechanical stability and higher union rates than the screw fixation alone for treating young patients with Pauwels type III femoral neck fractures (FNFs). No study has evaluated the effects of distal bicortical screw fixation and biomechanical properties of buttress plate augmentation under simultaneous vertical and rotational forces, physiologically acting on the hip joint. This study aimed to compare the biomechanical properties of four methods of three cannulated screw fixation under the combined axial and torsional loading in a synthetic femur model of type III FNF.Twenty-four third-generation composite femora were divided into four groups (6 femora in each group) based on the screw fixation configuration: inverted triangle configuration (Group A),  Pauwels' configuration (Group B), inverted triangle configuration combined with medial buttress plate using distal unicortical (Group C), and distal bicortical screw placement (Group D). A Pauwels type III FNF was simulated on the sawbones. Each model was subjected to the combined axial and torsional cyclic loading and subsequently tested to failure.Significant differences were determined in axial stiffness (AS) among the four groups (p = 0.024), whereas there was no significant difference in torsional stiffness (p = 0.147). The mean AS was higher in group D (639.5 ± 86.2 N/mm) than in group A (430.6 ± 94.8 N/mm), group B (426.2 ± 41.9 N/mm), and group C (451.2 ± 156.7 N/mm). Failure forces (FFs) were significantly different among four groups (p = 0.007), while there was no considerable difference in failure moment values (p = 0.555). The mean FF was significantly higher in group D (1307.1 ± 96.4 N) than in group A  (1076.9 ± 371.2 N) and group B (1075.5 ± 348.3 N) (p = 0.014 and p = 0.018, respectively). There was no significant difference in the mean FF between groups D and C.Regardless of the medial plate use, multiple cannulated systems could provide similar biomechanical results regarding torsional stiffness and failure moments. Bicortical placement of the most distal screw in medial buttress plate application could improve axial stability but not significantly affect the rotational stability of the inverted triangle screw fixation system in managing type III FNFs.
Keywords: Fracture Fixation, Internal; Bone Screws; Humans; Femur; Bone Plates; Biomechanical Phenomena; Femoral Neck Fractures